Validity and reliability of the Thai version of the stroke specific quality of life scale - ถ่างกระโทก ปราโมทย์; โพธิ์ใส วชิรา; พิพัฒน์สมบัติ เพลินตา; ไตรนาทถวัลย วินัย; สุขสถาน วานิช (Journal of Medicine and Health Sciences, 2019)
Abstract The objectives of this descriptive research study was to assess validity and reliability of the Thai version of the 12 items Stroke Specific Quality of Life Scale (Thai-SS-QoL-12). The 12 item Stroke Specific Quality of Life Scale (SS-QoL-12) was translated from English into Thai version. The content validity was validated based on index of item objective congruence (IOC) by five experts. The construct validity was analyzed by using confirmatory factor analysis (CFA) through LISREL. The reliability was validated based on Cronbach’s alpha reliability coefficient and corrected item-total correlation (CITC) method. Subjects of this study conducted in 140 patients with stroke at Sanpasithiprasong Hospital, Ubon Ratchathani, Thailand from September 2018 to January 2019. The content validity of the Thai-SS-QoL-12 was between 0.6 and 1.0 based on IOC by five experts. The validation of goodness of fitted model includes (χ2= 45.42, df = 45, p-value = 0.45434, χ2/df = 1.009, CFI = 1.00, GFI = 0.95, AGFI = 0.91, RMSEA = 0.0082). The SS-QoL-12 has constructed validity. The reliability of the scale was 0.94 based on Cronbach’s alpha reliability coefficient and CITCs were ranged between 0.67-0.83. Any items deletion did not result in an increase in Cronbach’s alpha. The Thai-SS-QoL-12 showed good validity and reliability. The scale could be used in stroke patients to assess health-related quality of life.